2011
DOI: 10.1088/0004-637x/729/1/69
|View full text |Cite
|
Sign up to set email alerts
|

A New Formation Scenario for the Milky Way Cluster NGC 2419

Abstract: We present a new formation scenario for NGC 2419, which is one of the most luminous, one of the most distant, and as well one of the most extended globular clusters of the Milky Way. We propose that NGC 2419 is the remnant of a merged star cluster complex, which was possibly formed during an interaction between a gas-rich galaxy and the Milky Way. To test this hypothesis, we performed numerical simulations of 27 different models of star cluster complexes (CCs) moving on a highly eccentric orbit in the Galactic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…We used the same seeds for the random number generator to generate the same distribution of star clusters scaled to the corresponding Plummer radius of the CC model. In a previous paper on the extended Milky Way cluster NGC 2419 (Brüns & Kroupa 2011), we have demonstrated that the exact initial distribution of star clusters in an extended CC leads to variations in the structural parameters mass and size of the order 10 to 20%. The initial velocity distribution of the CC models is chosen such that each CC is in virial equilibrium.…”
Section: Scenario and Model Parametersmentioning
confidence: 88%
“…We used the same seeds for the random number generator to generate the same distribution of star clusters scaled to the corresponding Plummer radius of the CC model. In a previous paper on the extended Milky Way cluster NGC 2419 (Brüns & Kroupa 2011), we have demonstrated that the exact initial distribution of star clusters in an extended CC leads to variations in the structural parameters mass and size of the order 10 to 20%. The initial velocity distribution of the CC models is chosen such that each CC is in virial equilibrium.…”
Section: Scenario and Model Parametersmentioning
confidence: 88%
“…The photometric catalogue is available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/ E-mail: mfrank@lsw.uni-heidelberg.de Present address: European Southern Observatory, Karl-Schwarzschild-Straße 2, 85748, Garching bei München, Germany 1 Throughout this paper we adopt a distance modulus of 19.71±0.08 mag for NGC 2419, measured by Di based on RR Lyrae; the distance of the Sun to the Galactic centre is assumed to be 8.3 kpc (Gillessen et al 2009). mer Milky Way satellite (e.g. van den Bergh & Mackey 2004), although to date no firm link with Galactic halo substructure, such as the Virgo, Gemini, Orphan, or Sagittarius streams has been established (Casetti-Dinescu et al 2009;Drake et al 2013;Brüns & Kroupa 2011;Casey et al 2014;Belokurov et al 2014). Given its unique location in the size-luminosity plane, it has also been suggested that NGC 2419 is a local example at the lowsurface-brightness end of the ultra-compact dwarf galaxy population (Brodie et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As noted in the introduction, Beccari et al (2011) Ripepi et al 2007;Cohen et al 2010;Brüns & Kroupa 2011;di Criscienzo et al 2011). For ωCen, Sollima et al (2007) found no difference in the luminosity function of stars in fields at 12 and 20 arcmin from the cluster center.…”
Section: Mass Segregation Vs the Non-concentrated Blue Straggler Popmentioning
confidence: 96%